2018
DOI: 10.1021/acs.energyfuels.8b02749
|View full text |Cite
|
Sign up to set email alerts
|

Study on MNO3/NO2 (M = Li, Na, and K)/MgO Composites for Intermediate-Temperature CO2 Capture

Abstract: Molten salt [MNO3/NO2 (M = Li, Na, and K)]-promoted MgO composite-type CO2 adsorbents with high capacity and cycling stability are fabricated by controlled hydrolysis along with an incipient impregnation approach. The remarkable results of molten salts on the CO2 capture performance of MgO adsorbents and the CO2 capture capacities with different loadings and calcination and adsorption temperatures were comprehensively investigated. Notably, optimized NaNO3-promoted MgO exhibited the highest CO2 capture capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…[26] The X-ray photoelectron spectroscopy (XPS) spectrum of fresh NaNO 2 -promoted MgO sample depicted in Figure 1b shows a peak at 403.8 eV, which is attributed to the N 1s core level of NO 2 − . [27] The N 1s peak was shifted from 403.8 eV before calcination to 407.4 eV after calcination, which is ascribed to the conversion of part of NaNO 2 to NaNO 3 [4,28] since the obtained X-ray photoelectron spectrum of the calcined material still showed a peak at 403.8 eV. This result is also in accordance with previously studied nitrite-promoted adsorbents, [9,29] though the NaNO 2 phase was not present in the XRD pattern after calcination.…”
Section: Structure and Surface Composition Of Molten-salt-promoted Mgosupporting
confidence: 88%
See 1 more Smart Citation
“…[26] The X-ray photoelectron spectroscopy (XPS) spectrum of fresh NaNO 2 -promoted MgO sample depicted in Figure 1b shows a peak at 403.8 eV, which is attributed to the N 1s core level of NO 2 − . [27] The N 1s peak was shifted from 403.8 eV before calcination to 407.4 eV after calcination, which is ascribed to the conversion of part of NaNO 2 to NaNO 3 [4,28] since the obtained X-ray photoelectron spectrum of the calcined material still showed a peak at 403.8 eV. This result is also in accordance with previously studied nitrite-promoted adsorbents, [9,29] though the NaNO 2 phase was not present in the XRD pattern after calcination.…”
Section: Structure and Surface Composition Of Molten-salt-promoted Mgosupporting
confidence: 88%
“…The latter is due to the lower diffraction intensities derived from the various planes of NaNO 2 and its smaller amount (wt%) present in the sample. [23,28] Scanning electron microscopy (SEM) studies were further conducted on NaNO 2 -promoted MgO after activation, and typical adsorbent agglomerated particles are shown in Figure S1a, Supporting Information. Furthermore, energy-dispersive X-ray spectroscopy (EDS) analysis (N, O, Na, and Mg) indicated that the molten salt was evenly dispersed on the MgO surface (Figure S1b, Supporting Information).…”
Section: Structure and Surface Composition Of Molten-salt-promoted Mgomentioning
confidence: 99%
“…Fortunately, doping alkali salts into MgO can significantly facilitate the sorption of CO 2 [20]. These alkali salts can be classified into four categories, i.e., single components [23][24][25][26][27], double salts [28][29][30][31], triple salts [32][33][34][35] and multiple salts [36,37]. For K 2 CO 3 -doped sorbents, recent studies indicate that the CO 2 sorption ability was increased to 10.2-11.7 wt% [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…The different promotion effects of these alkali metal nitrates can be associated with their different melting temperatures and the varied CO 2 solubility in these molten salts . It is indicated that the melting points of NaNO 3 , KNO 3 , and LiNO 3 are 307, 334, and 255 °C, respectively. , Compared to these single molten salts, the alkali metal nitrate eutectic mixtures show relatively lower melting points. For instance, the melting points of the binary nitrates of (K–Na)­NO 3 and (Li 0.44 K 0.56 )­NO 3 are 222 and ∼137 °C. , Theoretically, the binary molten salts should fuse more easily, allowing for facilitated CO 2 dissolution in the molten salts for improved carbonation reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…48 It is indicated that the melting points of NaNO 3 , KNO 3 , and LiNO 3 are 307, 334, and 255 °C, respectively. 39,49 Compared to these single molten salts, the alkali metal nitrate eutectic mixtures show relatively lower melting points. For instance, the melting points of the binary nitrates of (K−Na)NO 3 and (Li 0.44 K 0.56 )NO 3 are 222 and ∼137 °C.…”
Section: Resultsmentioning
confidence: 99%